Comparison of the Characteristics of Circulating Small Extracellular Vesicles Isolated by Ultracentrifugation and a Commercial Kit - Afrisham, Reza; Farrokhi, Vida; Moradi, Roya; Alizadeh, Shaban (Recent Patents on Biotechnology, 2025)
IntroductionThe market offers a wide range of extracellular vesicles (EVs) isolation products, but their lack of standardization is a concern. Therefore, it is important to carefully assess the quality of the EVs obtained using these products to patent the ideal method. In this study, we compared the EXOCIB kit with the ultracentrifuge method, which is considered the gold standard for small EV isolation.MethodsAfter overnight fasting, small plasma EVs were extracted from four individuals using both the ultracentrifuge and the EXOCIB kit methods. The pooled EVs were then compared for the presence of the cluster of differentiation 63 (CD63) protein using the western blot analysis, and their size and zeta potential were performed by Dynamic Light Scattering (DLS). In addition, the size and morphology of small EVs were determined by using the Transmission Electron Microscopy (TEM) technique.ResultsAn average hydrodynamic size of 135.7 nm and a zeta potential of -6.33 Mv at 25°C was found for small EVs isolated by the ultracentrifuge, whereas the kit method resulted in small EVs with a hydrodynamic size of 102.8 nm and a zeta potential of -0.907. Notably, the size of the particles in the kit samples was smaller compared to those obtained through the ultracentrifuge (P < 0.001). The western blot method confirmed the expression of CD63 in both methods, so the ultracentrifuge yielded small EVs with a higher level of purity compared to the kit-based approach (P = 0.036).ConclusionThe DLS findings revealed the existence of vesicles within the appropriate size range for small EVs like exosomes in both isolation techniques. The results of the western blot analysis, in conjunction with DLS, displayed that the ultracentrifuge method extracted small EVs with a greater degree of purity than the kit-based approach.
Keywords: ultracentrifugation